Nursing care of patients during the dying process: a painful professional and human function - Lopera Betancur, Martha Adiela (Investigación y Educación en Enfermería, 2015)
Objective. This work sought to describe the care functions of nurses with patients during the dying process. Methodology. This was a qualitative study with ethnographic approach stemming from the analysis of the culture of nurses; it was conducted in the city of Medellín, Colombia. Theoretical saturation was obtained with 23 interviews. Results. Nurses feel the duty to care for patients throughout the vital cycle through functions defined as: serving, helping, accompanying, offering support, advocating, educating, and representing, which they identify as indispensable. They also perceive as their own the social responsibility for some issues related to death and due to this they get involved at the personal level, appropriate care and are affected as persons. Conclusion. Patient care during dying processes transcends the limits of the nurse’s professional functions to become a human obligation. How to cite this article: Lopera MA. Nursing care of patients during the dying process: a painful professional and human function. Invest Educ Enferm. 2015; 33(2):